Early Maladaptive Schemas and Social Information Processing in Child-to-Parent Aggression. Issue 15 (August 2021) - Orue, Izaskun; Calvete, Esther; Fernández-González, Liria
The purpose of this longitudinal study was to assess the relationship between early maladaptive schemas (EMSs) and child-to-parent aggression (CPA) and to test whether social information processing (SIP) mediates this association. A total of 903 adolescents (50.9% girls) completed measures of EMSs at Time 1, SIP at Time 1 and Time 2 (1 year later), and CPA at Time 1, Time 2, and Time 3 (2 years later) to determine whether SIP measured at Time 2 mediated between the EMSs measured at Time 1 and CPA measured at Time 3. The results showed that each schema evaluated in this study had a different effect on SIP components and CPA. The SIP components of anger and aggressive response access in turn predicted CPA, mediating the relationship between two EMSs and CPA. More specifically, the schemas of defectiveness and the justification of violence predicted the response access component of SIP, which in turn predicted CPA. The results also showed bidirectional relationships between SIP components and CPA; whereas SIP components predicted CPA, the latter also predicted a worsening in SIP, perpetuating the problem. Furthermore, several gender differences were found in these paths. The findings indicate that intervention in the social-cognitive mechanisms is important to reduce adolescents' aggression directed toward their parents.